GA and RBFNN based PID for altitude-depth control of the multirotor Hybrid Aerial Underwater Vehicles. Issue 1 (1st April 2022) - Zongcheng, Ma; Xianyong, Jing; Zhuoran, Zhang; Shuchen, Xiao; Tian, Zhao; Guoshuai, Li
Abstract: Multirotor Hybrid aerial underwater vehicle (HAUV) is the vehicle which could operate both in air and underwater powered by multi-rotors. The water-air trans-domain process is very changeling for the change of the floatage and added mass and 'ground effect'. This paper researched on the effect of the intelligent algorithms on the trans-media control. And the genetic algorithm (GA) based and radial basis function (RBFNN) based proportional-integral-derivative (PID) controllers are developed for the trans-domain process. Then simulations and conclusions are made for these two controllers. It shows that the GA based PID controller is suitable for the trans-domain process. The RBFNN based PID controller could even do better work with the repeated optimized PID parameters value of GA. But one must pay attention to that the RBFNN-PID is very sensitive with the initial PID values. The initial values of PID parameters must be repeated optimized with GA to guarantee the better effect of the RBFNN-PID.